(untitled) (International Journal of Natural Sciences Research, 2022)
The aim of this study was to evaluate the Ecological Footprint (EF) for Environmental Sustainability in Ijebu Ode. The study adopted a descriptive cross-sectional study design and the objectives were, to assess the average EF of Ijebu Ode. Both primary and secondary data were employed, and the primary data for this study was collected from four hundred (400) systemically sampled households through structured questionnaires, and analysed descriptively using the Statistical Package for Social Sciences (version 20.0). The findings revealed the average ecological footprint of the Ijebu Ode to be 0.3gha per capita, with the footprint of water as the highest contributor to the EF, with 0.9gha (86.5%) of the total footprint. Thus, the study concluded that, the average EF of Ijebu Ode is 0.3 gha and therefore sustainable. However, it was recommended that, sustainable consumption must be encouraged, implemented and demonstrated to sustain the current EF of Ijebu Ode and public campaigns should be encouraged and implemented adequately in light of increasing awareness of the adverse environmental impacts of unsustainable consumption.